La armonía familiar y la dirección en una empresa familiar - Perez, Milagros (2019)
The majority of Peruvian companies are born being relatives. This characteristic makes them unique because they have institutions, leaderships and their own laws that must be managed so that they can survive, since the majority does not manage to pass to the second generation. This article provides an overview of management within a family business. For which an analysis is made on the conformation of a family business, to then analyze the government family business and the objectives that it pursues. Family harmony is the central axis to understand the dynamics within family businesses.